wing & wing (1971)
wing-and-wing A schooner has a mainsail, a foresail & a riding sail. When you're sailing with the wind and the mainsail is out at one side with the foresail out at the other, _or_ the foresail is out at one side with the riding sail out at the other, you say that you're sailing "wing & wing". JH APR 1971 Not used Not used Withdrawn withdrawn but no stamp